Corticotropin-releasing hormone: interactions with the immune system. - Tsagarakis, S; Grossman, A (1994)
Communication between the neuroendocrine and immune systems is crucial to host defence in both health and disease. Stress adversely interferes with the function of the immune system but the mechanism of such stress-induced immunosuppression is not well understood. Corticotropin-releasing hormone (CRH) is a 41-amino residue peptide which primarily stimulates ACTH secretion. In addition, CRH integrates a series of responses during the stress response. Over the last few years increasing evidence has suggested that CRH, the major stress-integrating peptide, may also directly modulate immune system function. Thus, recent data have demonstrated that CRH acts centrally as an immunosuppressant agent independent of circulating glucocorticoids. This central immunosuppressive effect of CRH is mediated at least partly via the central stimulation of sympathetic outflow. At a peripheral level, the presence of CRH and CRH receptors within cells of the immune system, and its complex effects directly on immune function, suggest that CRH is intimately associated with communication between the neuroendocrine and immune systems.